(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
This study investigates the process of root formation in microclonally propagated banana varieties under in vitro conditions. Banana production worldwide is significant, yet considered relatively low compared to other fruits, prompting the need for high-yielding, stress-resistant varieties and the development of efficient cultivation technologies. In vitro propagation of bananas is essential for mass production, but root formation can be hindered by the presence of high cytokinin levels. The research aims to optimize the cytokinin/auxin ratio in the rooting medium for successful root induction.